Pencak Silat Tournament Information System - Ari Kusuma Wardana; Eko Aribowo (Jurusan Teknik Informatika, 2021)
Purpose:This research was conducted to help manage the implementation of the pencak silat championship. So that the championship can run in an orderly and professional manner.Design/methodology/approach:This research went through several stages, starting from data collection, system requirements analysis, design, implementation, and system testing.Findings/result:Website-based information system for pencak silat tournament.Originality/value/state of the art:Pencak silat is a martial arts rich in techniques, benefits, and carries noble values that should be preserved as the Indonesian nation's successor. To preserve the existence of pencak silat in Indonesia, various pencak silat competitions were held in several cities in Indonesia. In the championship implementation, several things can disrupt the course of the matches. Of course, it will make the championship unprofessional. For this reason, along with the development of science and technology, a system was created that would help manage the implementation of the pencak silat championship so that the championship can run in an orderly and professional manner.